(3QSGdI aj CaVdjI GdJSHjMs - (3SdjeGf Hf YHO Gddg Hf Ydj Hf YeGQ GdHMQGfj GdeGMhRj,J (B1121 (3g` s
(3ChdgG (B:s
(3GdMeO ddg Ydi JMbjb GdeWGdH GdaGNQI hHYO agPG cdGe jSjQ ai CaVdjI GdJSHjM Ydi GdbQGAI s
(3BNQgG (B:s
(3Cf jWQMgG gPG GdbGFd jVYa SfOgG heNGdaJgG ddfUhU GdeYJHQI HGdhGQOGJ hGdNjQGJ HGdQGHYI hGdNGeSI ef GdKGfjI YTQI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B11s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B128 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B267s
Keywords: (3GdeLGejYs